Challenges and Management Strategies for Early Childhood Education in the Digital Era - Mohammad Zakki (SAHABAT: Jurnal Pendidikan Anak Usia Dini, 2025)
The digital era has brought significant changes to the management of Early Childhood Education (ECE), particularly in the field of educational management. Rapid technological development requires ECE institutions to adapt in order to maintain relevance and educational quality. However, in practice, ECE management still faces various challenges, including limited digital competencies among educators, inadequate technological infrastructure, curricula that are not fully adaptive, varying levels of parental involvement, and managerial leadership that remains largely conventional. This study aims to analyze the challenges and management strategies of Early Childhood Education in the digital era. The research employed a qualitative approach using a literature review method by analyzing relevant scientific articles, books, and academic journals. The findings indicate that effective management strategies include strengthening educators’ digital competencies, optimizing digital infrastructure, developing adaptive digital-based ECE curricula, enhancing partnerships with parents and the community, and reinforcing visionary leadership and digital-oriented managerial policies. These strategies are interrelated and play a crucial role in improving the quality of ECE services. This study is expected to contribute conceptually to ECE administrators in formulating adaptive and sustainable educational management policies in the digital era